Electronic Waste Valuation Analysis Supports A Circular Economy In Dki Jakarta - Indra Waharman (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to assess the valuation of electronic waste in DKI Jakarta using the Total Economic Value (TEV) approach to support circular economy implementation. The analysis compares direct value, indirect value, and standardized prices, while also evaluating the relevance of the TEV approach for economic decision-making among electronic waste management actors, particularly collectors. The study employed a cross-sectional mixed-methods design with data collected through field observations, transaction price records, document analysis, and questionnaires involving informal e-waste collectors. Descriptive statistical analysis using mean values and standard deviation was combined with TEV calculations to estimate the comprehensive economic value of electronic waste. The results indicate that collectors demonstrate high environmental awareness (mean = 3.92) and strong recognition of the social benefits of e-waste management (mean = 4.24). Knowledge of standardized e-waste prices is also relatively high (mean = 4.06). However, economic motivations remain dominant, as reflected by the moderate agreement that monetary value is more important than environmental impact (mean = 3.64). Perceptions regarding the usefulness of the TEV approach in determining purchase prices are relatively strong (mean = 3.90). Profitability perceptions vary across device categories, with used mobile phones (mean = 3.02) and large household appliances (mean = 3.04) considered more profitable than computers or laptops (mean = 2.18) and electronic cables (mean = 1.60). Overall, the findings demonstrate that the TEV-based valuation exceeds standardized market prices by incorporating environmental and social benefits that are not captured by conventional pricing mechanisms.